Breast Cancer: Making Sense of the Numbers - Martha C. Monroe; Barbara F. Shea; Linda B. Bobroff (EDIS)
This 6-page fact sheet helps people who have been diagnosed with breast cancer learn about the disease, and understand their diagnosis and treatment options. It is a minor revision written by Martha C. Monroe, Barbara F. Shea, and Linda B. Bobroff, and published by the Department of Family, Youth and Community Sciences, October 2017.